1994
DOI: 10.1021/np50104a002
|View full text |Cite
|
Sign up to set email alerts
|

Minor Constituents of Lippia integrifolia

Abstract: Three new sesquiterpenes (1-3) possessing the 2,6,6,9-tetramethyltricyclo[5 .4.0.0Z'*]undecane (lippifoliane) skeleton were isolated as minor constituents of Lippia integrifolia. Their structures and stereochemistry were elucidated from nmr data including double resonance experiments, COSY, and nOe, and by comparison of their "C-nmr spectra with those of lippifoli-1 (6)-en-5 -one.Following the studies on the chemical constituents of the aromatic shrub Lippiu integrifoo(iu (Griseb.) Hieron (Verbenaceae) (1-5), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…Partial catalytic hydrogenation of africa-1,5-diene (3) also afforded 2 and 7 (identified by GC-MS). The relative configurations of 2, 3, and 7 were thus confirmed by correlation with isoafricanol (6). Unfortunately, the absolute configuration is still unknown.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Partial catalytic hydrogenation of africa-1,5-diene (3) also afforded 2 and 7 (identified by GC-MS). The relative configurations of 2, 3, and 7 were thus confirmed by correlation with isoafricanol (6). Unfortunately, the absolute configuration is still unknown.…”
Section: Resultsmentioning
confidence: 71%
“…The structure of 5 was verified by 2D NMR techniques ( 1 H-1 H COSY, HMQC, HMBC, and NOESY). Catala `n et al reported the isolation of 3R-hydroxy-6-asteriscene from L. integrifolia 6 with a cis configuration of H-2 and H-9 (based on the large coupling constant of 11.0 Hz), as is the case in asteriscanolide, which has been studied by X-ray diffraction. 13 The coupling constant of 10.7 Hz between H-2 and H-9 observed in 5 (see the 1…”
Section: Resultsmentioning
confidence: 99%
“…Identification of the individual components was based on (a) computer matching with commercial mass spectra libraries (NBS75K, NIST, WILEY), [15][16][17] comparison with spectra available in our files [5][6][7][8]11,12 and literature data; [13][14][15][16][17][18] (b) comparison of their GC retention indices (RI) on an HP-5 column.…”
Section: Identificationmentioning
confidence: 99%
“…a Identification by comparison with mass spectrum reported in the literature 13. b Identification by comparison with mass spectra reported in the literature5,7,11,12,21 and in our files. c Known also as bulnesol.…”
mentioning
confidence: 92%
“…2 Subsequently, the research groups of Catalan and Joseph-Nathan reported the isolation of three more derivatives of lippifolianes 5-7, Chart 1. 3 Recently, the absolute configuration of lippifolianes along with that of the africananes have been assigned by JosephNathan et al on the basis of the analysis of circular dichroism data in combination with density functional theory minimum energy molecular models. 4 The tricyclo [5.4.0.0 2,4 ]undecane 1 was also present as an integral part in a few diterpenoids.…”
Section: Introductionmentioning
confidence: 99%